AI for Inclusive Learning: A Review of Adaptive Technologies for Disabled Students - Eviyona Laurenta Br Barus; Wawan Bunawan; Dimas Ridho (Jurnal Penelitian Pendidikan IPA, 2025)
This paper explores the intersection of artificial intelligence (AI) and inclusive education, focusing on how AI technologies support learning for students with disabilities. AI-driven tools, such as intelligent tutoring systems, speech-to-text applications, and text-to-speech readers, offer personalized, adaptive, and accessible learning experiences. These tools enhance academic engagement and foster independence for students with cognitive, sensory, or physical disabilities. A systematic literature review of recent studies (2020–September 2025) was conducted, analyzing research from the fields of education, health, and technology to identify trends, benefits, and challenges. The review reveals growing interdisciplinary interest; key results indicate that while AI enhances student engagement and independence, significant challenges remain. The paper concludes that AI, when developed responsibly and used collaboratively, has the potential to transform inclusive education, but requires supportive policies, ethical frameworks, and equitable access. The findings emphasize the central role of teachers in guiding AI implementation and interpreting its outputs. It is concluded that AI has vast potential to transform inclusive education, but realizing this requires supportive policies, robust ethical frameworks, and equitable access, ensuring teachers remain central to the learning process.